The Role of the Heritage Center Against the Embezzlement of Assets by Guardians of Minors: Study at the Medan Heritage Center - Siahaan, Shinta Romaito; Habeahan, Besty (Manunggal Halim Jaya, 2025)
The heritage center (BHP) plays a central role in safeguarding and managing inheritances, especially for minors who are not yet able to manage their own assets. BHP was established in 1624 by the Dutch Government, with the aim of protecting the assets of the deceased, especially for orphans and those under guardianship. In Indonesia, BHP is under the Directorate General of General Legal Administration, Ministry of Law and Human Rights, with authority regulated through various legal regulations. One of the main roles of BHP is to supervise guardians, as stipulated in Article 366 of the Civil Code, who are responsible for managing the assets of minors who are not under parental supervision. This study aims to evaluate the role of BHP in preventing misuse of minors' assets by guardians, as well as identifying obstacles faced in carrying out supervision. Using normative methods through literature studies, this study analyzes the legal aspects underlying the function of BHP. The results of the study indicate that BHP plays an important role in supervising the management of children's assets through inventories and annual reports by guardians. However, cases of misuse of assets by guardians still often occur due to weak supervision and loopholes in the legal system.